2001
DOI: 10.1063/1.1363604
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic modeling of the effects of stress on magnetic properties

Abstract: A micromagnetic model has been developed for investigating the effect of stress on the magnetic properties of thin films. This effect has been implemented by including the magnetoelastic energy term into the Landau-Lifshitz-Gilbert equation. Magnetization curves of a nickelfilm were calculated under both tensile and compressive stresses of various magnitudes applied along the field direction. The modeling results show that coercivity increased with increasing compressive stress while remanence decreased with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…4(b)), since increase of compressive stress ðso0Þ across stripe causes gradual depletion of domains with magnetization oriented along the field direction. The strain-induced enhancement of coercive field can be discussed in the frame of Garshelis predictions [21]: tensile stress along field direction leads to an increase of coercivity if magnetization reversal mechanism is dominated by irreversible rotation of domains [4,25]. Although this criterion can be met in our H k case (see Fig.…”
Section: Article In Pressmentioning
confidence: 91%
“…4(b)), since increase of compressive stress ðso0Þ across stripe causes gradual depletion of domains with magnetization oriented along the field direction. The strain-induced enhancement of coercive field can be discussed in the frame of Garshelis predictions [21]: tensile stress along field direction leads to an increase of coercivity if magnetization reversal mechanism is dominated by irreversible rotation of domains [4,25]. Although this criterion can be met in our H k case (see Fig.…”
Section: Article In Pressmentioning
confidence: 91%
“…Thus an electric fi eld control of the magnetic behavior of the magnetic nanostructures can be achieved by such a strain-mediated ME coupling, as observed recently by many researchers. [190][191][192][193][194][195][196][197][198][199] Actually, based on the previous experimental observation, magnetization reorientation and coercive force can be induced by tuning the fi lm strains externally in many ferromagnetic thin fi lms, [200][201][202][203][204] when such strain-induced change is caused by applying electric fi eld to a piezoelectric layer, then the ME coupling-induced magnetic switching takes place.…”
Section: Strain-mediated Me Effectmentioning
confidence: 99%
“…In fact, the experiment results [9,10] indicated that both the strains and the magnetization are strongly coupled with the bias magnetic field and the pre-stress (it is called compressive stress when the stress is smaller than zero (so0) and tension stress when the stress is larger than zero ðs40Þ). As for the effect of pre-stress on the magnetization, Jiles et al [22][23][24][25][26][27][28] pointed out that this effect is mainly a result of the influence of the pre-stress on the magnetostrictivity. According to this viewpoint, Jiles et al [22] presented a magnetization model on the basis of a fitting formula of the curves of magnetostrictive strain in terms of magnetization.…”
Section: Introductionmentioning
confidence: 97%